Factors influencing the occurrence of traffic accidents in urban roads: A combined GIS-Empirical Bayesian approach (2016)
The problem of urban road accidents in Colombia is remarkable and has a significant magnitude. For this reason, a technical study of this important public health scourge is important. The quantitative techniques employed are usually highly aggregated and will not correctly identify the determinant variables of the problem. This paper examines the relationship between urban road accidents and variables related to road infrastructure, environment, traffic volumes and traffic control. Some accident-prone sections in the city of Cartagena (Colombia) are specifically identified by the empirical Bayesian method based on GIS. A total of 69 accident-prone sections were identified in the city. It was evident that the marginal effect on the accident rate for motorcycles is well above that for cars and buses. Empirical evidence also showed that the sections located in commercial areas tend to have higher frequency of accidents due to the high presence of pedestrians.